Analysis of cocaine, benzoylecgonine ecgonine methyl ester, and ecgonine by high-pressure liquid chromatography-API mass spectrometry and application to a short-term degradation study of cocaine in plasma - Klingmann, Andrea; Skopp, Gisela; Aderjan, Rolf (Journal of analytical toxicology, 2001)
A method for the determination of cocaine (COC), benzoylecgonine (BE), ecgonine methyl ester (EME), and ecgonine (ECG) in plasma by liquid chromatography-mass spectrometry (LC-MS-MS) was developed. The analytes were isolated from human plasma by subsequent solid-phase extraction and were separated on a Zorbax Eclipse XDB-C8 narrow-bore column using an ammonium acetate buffer/acetonitrile/methanol gradient. A Turbolonspray® source was used for ionization. The analytes were characterized by their particular molecular ion and several fragments. Multiple reaction monitoring (MRM) was used for isolation and quantitation. The assay was rapid, highly sensitive, and reliable. The method was applied to monitor the in vitro degradation of cocaine in plasma. Fresh unpreserved and preserved (0.25 % KF) plasma samples were spiked with 1000 ng cocaine/mL. Aliquots of both series were stored at 4°C and 20°C and were analyzed at selected storage times of up to 15 days. In all samples, degradation of cocaine that was dependent on storage time and temperature and on sample preservation could be observed. The formation of BE did not occur to a significant extent (< 12%, referred to the initial concentration of COC), and its concentration was slightly higher in preserved compared with unpreserved plasma at both storage temperatures chosen. EME was formed in considerably higher amounts compared to BE. As already observed for COC, its formation and degradation were dependent on storage time, temperature, and preservation. EME is suggested to be the major source of ECG, which was detectable in all samples after 1-2 days of storage. Although the degradation of COC was shown to be highly dynamic in nature, the sum of all hydrolysis products of COC accounted for the initial COC concentration at any particular time of storage. Therefore, production of hitherto unknown degradation products of COC seems unlikely. Moreover, the common transformation product of BE and EME appeared to he stable, and ECG is suggested as a promising postcollection artifact.
Gesehen am 28.04.2021